Pancatransformasional Leadership in Madrasahs: Integrating Religious Values for Sustainable Environmental Education through Adiwiyata Programs - Yaqin, Firdaus Ainul; Mulyadi, Mulyadi; Marno, Marno (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the characteristics of the transformational leadership of the madrasah principal in the development of Madrasah Adiwiyata. This study uses a qualitative approach of the case study type through a multi-site approach. Data collection techniques include in-depth interviews, participatory observation, and documentation. Data analysis techniques use an interactive model consisting of four stages: data collection, data presentation, data condensation, and concluding. The study results indicate that The 4